2022-RA-1301-ESGO The impact of hospital surgical volume on survival in early-stage cervical cancer treated with radical hysterectomy: a sub-analysis of the SCCAN study. (20th October 2022) - Bizzarri, Nicolò; Dostálek, Lukáš; Lonkhuijzen, Luc RCW; Giannarelli, Diana; Lopez, Aldo; Falconer, Henrik; Querleu, Denis; Ayhan, Ali; Kim, Sarah H; Ortiz, David Isla; Klat, Jaroslav; Obermair, Andreas; et al.
Abstract : Introduction/Background: The objective was to evaluate the impact of number of radical hysterectomies (RHs) performed per year in each center on disease-free survival (DFS) and overall survival (OS), from patients previously included in the SCCAN study. Methodology: International, multicenter, retrospective study. Patients with FIGO-2009-stage IB1-IIA1 cervical cancer who underwent RH, did not undergo neo-adjuvant chemotherapy and with pathologic negative lymph nodes, were included. Patients were treated in national referral centers for gynecologic oncology according to updated national/international guidelines. Optimal cut-offs for surgical volume were identified using an unadjusted Cox proportional hazard model with DFS as outcome and defined as the value which minimizes the p-value of the split in groups in terms of DFS. A Propensity Score Matching (PSM) was used to adjust the differences between the groups baseline characteristics. Results: 2, 157 patients were initially included. The two most significant cut-offs for surgical volume were identified in 7 and 17 surgical procedures, dividing the entire cohort in low, middle, and high-volume centers. After PSM, 1, 238 patients, distributed as 619 (50.0%) in high-volume, 523 (42.2%) in middle-volume and 96 (7.8%) in low-volume group, were analyzed. Patients operated in higher volume institutions had a progressively better 5-year DFS than those operated in lower volume centers (92.3% vs 88.9% vs 83.8%, p=0.029). No 5-year OS difference was noted (95.9% vs 97.2% vs 95.2%, p=0.70). Cox multivariate regression analysis for risk of showed that FIGO-stage >IB1, LVSI+, grade >1, tumor diameter >20 mm, minimally invasive approach, non-squamous cell histology, and lower volume centers represented independent risk factors for recurrence. Conclusion: Surgical volume represented an independent prognostic factor affecting DFS. Increasing number of RHs performed in each center every year was associated with improved DFS. Performance of at least 18 RHs per year may be considered the target volume of cases for referral centers associated with better DFS.